A New Approach to Solve Multi Objective Linear Programming Problem Under Neutrosophic Environment - Biswas, Sanjoy; Dey, Samir (International journal of applied and computational mathematics, 2023)
In the present era, the idea of nonlinearity plays a crucial and fundamental role in an intuitionistic fuzzy world. The goal of this paper is to develop some novel and valuable concepts for the ability to effectively convey challenging and ambiguous information in real life issues. In order to achieve this goal, this work investigated the interval valued pentagonal intuitionistic fuzzy multi-objective linear programming problem under neutrosophic uncertainty. This study provides solutions to such uncertainty and assists in the relative decision-making processes. The major objective of this paper is to develop some novel and useful concepts of nonlinear interval valued pentagonal intuitionistic fuzzy numbers and their classification in different situations. Additionally, the new de-intuitification (Ranking) method is formulated in decision-making by reducing complexions and addresses the graphical illustration. The proposed technique based on neutrosophic fuzzy approaches provides the potential value to decision makers of optimization problems under three distinct membership degrees, such as truth, indeterminacy, and falsity membership degrees. Therefore, this paper implemented methodologies with the help of numerical examples and addressed the effectiveness of several membership functions as linear, parabolic, and hyperbolic types of membership functions. A comparative study of existing approaches has been done to show the efficiency of the proposed approach. Finally, based on suggested study, conclusions and future research directions are discussed.